What is 1 minus 6/9?
Looking for the result of 1 - 6/9? Follow this step-by-step guide to understand how to subtract these two fractions.
How to subtract 1 by 6/9?
- Multiply the numerator of the first term, with the denominator of the second term: 1 × 9 = 9
- Multiply the numerator of the second term, with the denominator of the first term: 6 × 1 = 6
- Subtract both of these results together to form the new numerator: 9 − 6 = 3
- Multiply both denominators together to form the new denominator: 1 × 9 = 9
- Combine the results to get the new fraction: 3/9
- Simplify the fraction (3/9) by dividing both the numerator and the denominator by their GCD (3):
- 3/3 = 1
- 9/3 = 3
- This gives: 1/3.
The result of subtracting 1/1 and 6/9 is : 1/3 (or 0.33333333333333 in its decimal form)